2008
DOI: 10.1007/s11242-008-9253-5
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Convection Heat Transfer in the Annulus Between Two Concentric Vertical Cylinders Using Porous Layers

Abstract: A numerical investigation of the steady-state, laminar, axi-symmetric, mixed convection heat transfer in the annulus between two concentric vertical cylinders using porous inserts is carried out. The inner cylinder is subjected to constant heat flux and the outer cylinder is insulated. A finite volume code is used to numerically solve the sets of governing equations. The Darcy-Brinkman-Forchheimer model along with Boussinesq approximation is used to solve the flow in the porous region. The Navier-Stokes equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Three porous inserts are attached at the inner cylinder of the annulus in the form of porous rings and the flow equations are solved by considering two different set of equations for fluid and porous domains. Later, Al-Zahrani and Kiwan [23] numerically analyzed the mixed convection in an open-ended vertical annulus with a porous layer attached to the outer surface of the inner cylinder. They considered the Darcy-Brinkman-Forchheimer model for the porous region and the Navier-Stokes equation for the clear fluid region, and found that the heat transfer can be enhanced by using porous layers of high thermal conductivity ratios.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three porous inserts are attached at the inner cylinder of the annulus in the form of porous rings and the flow equations are solved by considering two different set of equations for fluid and porous domains. Later, Al-Zahrani and Kiwan [23] numerically analyzed the mixed convection in an open-ended vertical annulus with a porous layer attached to the outer surface of the inner cylinder. They considered the Darcy-Brinkman-Forchheimer model for the porous region and the Navier-Stokes equation for the clear fluid region, and found that the heat transfer can be enhanced by using porous layers of high thermal conductivity ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Relative to a large volume of investigations in the porous annulus, we noticed that the preceding works on natural convection in a vertical porous annulus are limited to uniform heating of the inner wall by either isothermal or isoflux wall-heating conditions [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. However, in many practical applications, heating takes place over a portion of one of the vertical walls, where the size and location of the heating segment may significantly affect the heat transport process in the annular enclosure filled with a fluid-saturated porous media.…”
Section: Introductionmentioning
confidence: 99%
“…Among the finite porous enclosures, free convective heat transfer in a differentially heated vertical porous annulus has received considerable attention owing to its importance in high performance insulation for buildings and porous heat exchangers (Hickox and Gartling 1985;Char and Lee 1998;Al-Zahrani and Kiwan 2009;Shivakumara et al 2003;Prasad 1986). Natural convection in square and rectangular porous enclosures subject to discrete heating has drawn much attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…They found that for a low thermal conductivity ratio, the difference between fluid and solid temperatures was at its highest level. Al Zahrani et al 4 performed an analysis of the mixed convection in the porous space between twain concentric cylinders. The obtained results show that if the thermal conductivity ratio is further than its critical value, the average Nusselt number decreases.…”
Section: Introductionmentioning
confidence: 99%